PENGUATAN SEKTOR EKONOMI LOKAL BERBASIS TRI HITA KARANA (MILO SITANA) - D. Marsadi; I.M. Sila; I.K.S Adnyana; G. Sedana; I.W. Dirgayana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Puhu Village has abundant local potential, one of which is the Micro Business of processing buntilan, jaje uli (ceremonial facilities) and generators. Micro business development carried out by the community in Puhu Village experienced many obstacles. This service aims to produce buntilan preservation technology and produce jaje uli drying technology by utilizing fuel from livestock waste (biogas) in Puhu Village, Payangan District, Gianyar Regency. This service is carried out through the stages of discussion, socialization, training and mentoring. The program carried out in Puhu Village has been going well and is on target. There were two activities carried out and they became a solution to the problems in Puhu Village. The first activity was training in preserving the buntilan by boiling the cornhusk and doing airtight packaging. The second activity is making jaje uli drying machine by utilizing livestock waste as an energy source. Buntil maintenance activities are able to extend the shelf life, which previously lasted for about one day, now it can last for three to four days. Making jaje uli drying machines by utilizing livestock waste as an energy source provides benefits where previously jaje uli makers were only able to produce in sunny weather because in the drying process utilizing sunlight now jaje uli makers are able to dry jaje uli in the rainy season with a shorter time. Keywords : Puhu Village, Jaje Uli, Drying Machine, Buntilan Preservation